RELATIONSHIP BETWEEN SEDIMENT ORGANIC MATERIAL CONTENT WITH THE ABUNDANCE OF Cerithidea obtuse IN THE INTERTIDAL ZONE, BUKIT BATU DISTRICT, BENGKALIS REGENCY, RIAU - Parapat, Monica Esra; Nasution, Syafruddin; Zulkifli, Zulkifli (Asian Journal of Aquatic Sciences, 2024)
This study was carried out in March-April 2024 in the intertidal zone of Bukit Batu District, Bengkalis Regency, Riau Province, with the aim of knowing the size distribution and the relationship between sediment organic matter content and the abundance of C. obtusa. This research uses a survey method by determining sampling stations using purposive sampling consisting of three stations. Each station has three transects consisting of plots measuring 3 m2. To determine differences in abundance, the Kruskal Wallis test was carried out and to determine the relationship between sediment organic matter content and the abundance of C. obtusa, statistical correlation and linear regression tests were carried out. The results showed that the organic matter content of the sediment is included in the medium-high category, ranging from 15.82%-22.27%. The abundance of C. obtusa ranged between 5.12−6.96 ind/m2. There were differences in the abundance of C. obtusa among stations, with details between stations 3 and 1 and stations 3 and 2 being significant, while between stations 1 and 2 it was not significant. There were no differences in the abundance of C. obtusa among intertidal subzones. The distribution of C. obtusa is clustered with a dominant size of 20.7−34.5 mm. There is a moderate relationship between sediment organic matter content and the abundance of C. obtusa with a correlation coefficient (r) of 0.4743 and interpreted in the equation Y = -0,0009 + 0,2775X